Short‐term adaptation and chronic cardiac remodelling to high altitude in lowlander natives and Himalayan Sherpa. Issue 11 (20th November 2014) - Stembridge, Mike; Ainslie, Philip N.; Shave, Rob
Abstract : New Findings: What is the topic of this review? At high altitude, the cardiovascular system must adapt in order to meet the metabolic demand for oxygen. This review summarizes recent findings relating to short‐term and life‐long cardiac adaptation to high altitude in the context of exercise capacity. What advances does it highlight? Both Sherpa and lowlanders exhibit smaller left ventricular volumes at high altitude; however, myocardial relaxation, as evidenced by diastolic untwist, is reduced only in Sherpa, indicating that short‐term hypoxia does not impair diastolic relaxation. Potential remodelling of systolic function, as evidenced by lower left ventricular systolic twist in Sherpa, may facilitate the requisite sea‐level mechanical reserve required during exercise, although this remains to be confirmed. Both short‐term and life‐long high‐altitude exposure challenge the cardiovascular system to meet the metabolic demand for O2 in a hypoxic environment. As the demand for O2 delivery increases during exercise, the circulatory component of oxygen transport is placed under additional stress. Acute adaptation and chronic remodelling of cardiac structure and function may occur to facilitate O2 delivery in lowlanders during sojourn to high altitude and in permanent highland residents. However, our understanding of cardiac structural and functional adaption in Sherpa remains confined to a higher maximal heart rate, lower pulmonary vascular resistance and no differences in resting cardiac output. Ventricular form and function are intrinsically linked through the left ventricular (LV) mechanics that facilitate efficient ejection, minimize myofibre stress during contraction and aid diastolic recoil. Recent examination of LV mechanics has allowed detailed insight into fundamental cardiac adaptation in high‐altitude Sherpa. In this symposium report, we review recent advances in our understanding of LV function in both lowlanders and Sherpa at rest and discuss the potential consequences for exercise capacity. Collectively, data indicate chronic structural ventricular adaptation, with adult Sherpa having smaller absolute and relative LV size. Consistent with structural remodelling, cardiac mechanics also differ in Sherpa when compared with lowlanders at high altitude. These differences are characterized by a reduction in resting systolic deformation and slower diastolic untwisting, a surrogate of relaxation. These changes may reflect a functional cardiac adaptation that affords Sherpa the same mechanical reserve seen in lowlanders at sea level, which is absent when they ascend to high altitude. Abstract :